Formulation, optimization and characterization of palm kernel oil esters nanoemulsion system containing sodium diclofenac - Rezaee, Malahat (2014)
Nanoemulsions are nano-size emulsions which are used in many applications such as cosmetics and pharmaceuticals as delivery systems for parenteral, oral, ocular or transdermal administration. Transdermal administration is a suitable route for sodium diclofenac to prevent its adverse side effects which exhibited in other routes. Palm kernel oil esters (PKOEs) were selected as the oil phase for the preparation of nanoemulsion formulations containing sodium diclofenac. Special characteristic of PKOEs which has been reported is excellent wetting behavior without the oily feeling which makes it suitable for delivery of actives. Ternary phase diagrams of palm kernel oil esters with three surfactants (lecithin, Tween 20, Cremophor EL) as single and binary surfactants were constructed in three systems. The binary systems consisted of lecithin/Tween 20 and lecithin/Cremophor EL in two ratios of 80:20 and 60:40 for both systems. The increase of hydrophilic lipophilic balance (HLB) value and synergism effect between the surfactants in the binary surfactants systems gave larger homogenous and isotropic phases. The isotropic region in the PKOEs/Lecithin:Cremophore EL (60:40)/water system was selected as nano-size emulsions composition range to be optimized and evaluated for their independent variables on responses of particle size and viscosity using Response Surface Methodology. The independent variables were water content, oil and surfactant ratio, stirring rate and stirring time. The study showed that third-order polynomial model was sufficient to describe and predict the responses. The smallest P-value and largest F-value belonged to O/S ratio for both responses. The optimized formulation (Opt.F) was formulated based on the achieved optimum conditions for preparation of sodium diclofenac nanoemulsions with the lowest values of particle size and viscosity to provide better drug penetration. As the O/S ratio was found to be the most efficient factor on the particle size and viscosity, in addition of Opt.F, five other formulations with different O/S ratio were selected for characterization. The stability of the all formulations was evaluated by centrifugation, freeze-thaw cycle test and storage stability test. The Opt.F depicted good stability through the stability tests with no phase separation. The F-3 and F-4 formulations exhibited better stability than the other formulations. Rheology study showed that all nanoemulsion formulations exhibited non-Newtonian flow behaviour by displaying a pseudoplastic behaviour. Aerobic plate count, and yeast and mould count tests showed that there were no bacteria and fungus growth in the samples. The nanoemulsion formulations were found to be non-irritating by Irritancy Test. Permeation study was carried out by using cellulose acetate membrane and Wistar male rat skin. Opt.F and F-2 had the higher percentage of drug release. Five different terpenes based on the different chemical structure in five different concentrations were chosen as enhancer in Opt.F. All terpenes showed promoting effect on sodium diclofenac penetration. In addition, increase in terpenes concentration exhibited enhancement effect on drug permeation. Menthol had the highest permeation coefficient with the highest enhancement ratio for penetration of sodium diclofenac. Menthol and menthone in all concentrations of terpenes were shown to have significant effect on sodium diclofenc permeation. Different ratio of O/S is an effective factor on drug permeation. In conclusion, nanoemulsion formulations with good stability and suitable properties for transdermal delivery of sodium diclofenac were designed and developed.